Choroidal and Retinal Thickness of Highly Myopic Eyes with Early Stage of Myopic Chorioretinopathy: Tessellation - Yanping Zhou; Minlu Song; Minwen Zhou; Yiming Liu; Fenghua Wang; Xiaodong Sun (Journal of Ophthalmology)
Purpose. To investigate the choroidal thickness (CT) and retinal thickness (RT) in highly myopic tessellated eyes. Methods. In this study, 115 highly myopic eyes were recruited and divided as tessellated fundus (n=93) and normal fundus (n=22). RT and CT were quantified using optical coherence tomography with enhanced depth imaging (EDI-OCT). Correlation between subfoveal CT (SFCT) and tessellation was analyzed using logistic regression models. Results. Tessellated fundus eyes had thinner CT than did normal fundus eyes, while RT was not statistically different across groups. The tessellated eyes had a thinner choroid than did the control eyes at all measured macular locations (all P<0.05). After adjustment for AL, age, and gender, the SFCT was significantly associated with tessellation. The odds ratio (OR) and 95% confidence interval (CI) was 0.975 (0.960–0.990, P=0.001, binary logistics regression) and 0.991 (0.984–0.999, P=0.022, Cox regression). The area under the curve (AUC) of SFCT was the greatest for detecting tessellation (AUC = 0.824, P<0.001). For sensitivity and specificity analyses, SFCT had the highest diagnostic value (sensitivity = 81.8%, specificity = 74.2%). Conclusions. Highly myopic eyes with tessellation have thinner CT than do normal highly myopic eyes. CT may serve as an early pathologic predictor of high myopia.